Development and validation of a sensitive liquid chromatographic–tandem mass spectrometric method for the simultaneous analysis of granisetron and 7‐hydroxy granisetron in human plasma and urine samples: application in a clinical pharmacokinetic study in pregnant subject. (21st July 2015) - Zhao, Yang; Chen, Hui‐Jun; Caritis, Steve; Venkataramanan, Raman
Abstract: A liquid chromatography–tandem mass spectrometric method for the quantification of granisetron and its major metabolite, 7‐hydroxy granisetron in human plasma and urine samples was developed and validated. Respective stable isotopically labeled granisetron and 7‐hydroxy granisetron were used as internal standards (IS). Chromatography was performed using an Xselect HSS T3 analytical column with a mobile phase of 20% acetonitrile in water (containing 0.2 mM ammonium formate and 0.14% formic acid, pH 4) delivered in an isocratic mode. Tandem mass spectrometry operating in positive electrospray ionization mode with multiple reaction monitoring was used for quantification. The standard curves were linear in the concentration ranges of 0.5–100 ng/mL for granisetron and 0.1–100 ng/mL for 7‐hydroxy granisetron in human plasma samples, and 2–2000 ng/mL for granisetron and 2–1000 ng/mL for 7‐hydroxy granisetron in human urine samples, respectively. The accuracies were >85% and the precision as determined by the coefficient of variations was <10%. No significant matrix effects were observed for granisetron or 7‐hydroxy granisetron in either plasma or urine samples. Granisetron was stable under various storage and experimental conditions. This validated method was successfully applied to a pharmacokinetic study after intravenous administration of 1 mg granisetron to a pregnant subject. Copyright © 2015 John Wiley & Sons, Ltd.